A catered bake-off - Crawford, Isis (Crawford, Isis. Mystery with recipes, 2025)
Sisters Bernie and Libby Simmons's baking competition sours with suspicious ingredients, malfunctioning appliances, a goat invasion, and ominous notes delivered to the cast and crew--and when a judge meets a grisly end, the sleuthing siblings race to catch a mixed-up killer.